2019
DOI: 10.1523/jneurosci.2112-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Going with the Flow: The Neural Mechanisms Underlying Illusions of Complex-Flow Motion

Abstract: Studying the mismatch between perception and reality helps us better understand the constructive nature of the visual brain. The Pinna-Brelstaff motion illusion is a compelling example illustrating how a complex moving pattern can generate an illusory motion perception. When an observer moves toward (expansion) or away (contraction) from the Pinna-Brelstaff figure, the figure appears to rotate. The neural mechanisms underlying the illusory complex-flow motion of rotation, expansion, and contraction remain unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 108 publications
(140 reference statements)
1
17
0
Order By: Relevance
“…Neurons in MT are strongly selective for motion direction ( Albright, 1989 ; Albright et al, 1984 ; DeAngelis & Uka, 2003 ; Desimone & Ungerleider, 1986 ; Maunsell & Van Essen, 1983 ; Van Essen et al, 1981 ; Zeki, 1974 ) and speed ( DeAngelis & Newsome, 1999 ; Liu & Newsome, 2003 ; Maunsell & Van Essen, 1983 ). MT activity reflects perceived motion direction ( Britten, Newsome, Shadlen, Celebrini, & Movshon, 1996 ; Purushothaman & Bradley, 2005 ), even when the perceived motion does not correspond with retinal image motion ( Krekelberg, Dannenberg, Hoffmann, Bremmer, & Ross, 2003 ; Luo et al, 2019 ; Rodman & Albright, 1989 ; Stoner & Albright, 1992 ). If MT represents the result of flow parsing, the observed biases in perceived object direction should correspond to a shift in MT's population response profile, when plotted as a function of direction preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons in MT are strongly selective for motion direction ( Albright, 1989 ; Albright et al, 1984 ; DeAngelis & Uka, 2003 ; Desimone & Ungerleider, 1986 ; Maunsell & Van Essen, 1983 ; Van Essen et al, 1981 ; Zeki, 1974 ) and speed ( DeAngelis & Newsome, 1999 ; Liu & Newsome, 2003 ; Maunsell & Van Essen, 1983 ). MT activity reflects perceived motion direction ( Britten, Newsome, Shadlen, Celebrini, & Movshon, 1996 ; Purushothaman & Bradley, 2005 ), even when the perceived motion does not correspond with retinal image motion ( Krekelberg, Dannenberg, Hoffmann, Bremmer, & Ross, 2003 ; Luo et al, 2019 ; Rodman & Albright, 1989 ; Stoner & Albright, 1992 ). If MT represents the result of flow parsing, the observed biases in perceived object direction should correspond to a shift in MT's population response profile, when plotted as a function of direction preferences.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between RF eccentricity and RF size in the MST is weaker (24,31,34,38,51,52) than that found in the neurons of lower areas [see, e.g., Fig. 1 of Freeman and Simoncelli (53)].…”
Section: Receptive Fields: Size Shape and Structurementioning
confidence: 99%
“…It is also worth noting that for both-motions optimized stimuli, there was no "additive" effect for combining diagonal and lateral illusory motion together. We do not wish to suggest that we can infer directly from single unit responses to global illusory perception, but previous work has shown that biases present in neurons in early visual areas can be combined downstream in MT and MST to form global perceptions of illusory motion (Luo et al, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We used control stimuli whose illusory contours are orthogonal to the line patterns ( Supplementary Figure 5 top row), where only the physical direction of line pattern motion should be observed in the direction tuning curve of modeled neurons. For stimuli that contain a single tilt (Supplementary Figure 5 middle row), if the energy model is consistent with illusory perception, we predict that the tuning curves will shift clockwise or anti-clockwise depending on the combination of tilt and physical motion direction (for details of how predictions are made please refer to Luo et al, 2019). For the zigzag patterns ( Supplementary Figure 5 bottom row), both clockwise and anti-clockwise relative illusory motions are present and should therefore cause an increase in bandwidth without an overall shift in preferred direction.…”
Section: Experiments 6 Spatiotemporal Energy Modelmentioning
confidence: 94%
See 1 more Smart Citation